Revisiting early Political History of Modern Sarawak through the making of Stephen Kalong Ningkan as Sarawak’s first Chief Minister - Stanley Bye, Kadam Kiai; Dick Lembang, Dugun (Institute of Borneo Studies, UNIMAS, 2020)
This paper narrates a political story of modern Sarawak from 1961 to 1974. The modern political history of Sarawak began with the conceptualisation and the formulation of the Federation Malaysia. The significant events that shaped and influenced the political history of modern Sarawak include: the British-Malayan Government meetings in November 1961 and July 1962; the setting up of the Cobbold Commission of Enquiry; the formulation of the MalaysiaSolidarity and Consultative Committee (MSCC); the formation of the Inter-Governmental Committee (IGC); the signing the Malaysia Agreement of 1963; the controversies surrounding the making of the first Chief Minister and of the making of the first local State Governor; the cabinet crises of 1965 and 1966; the proclamation of the state of emergency in Sarawak in 1966 by the Federal Parliament which led to the removal of its first Chief Minister; and the establishment of the Sarawak Alliance and the Native Alliance. This historical account of the early history of modern Sarawak is not complete without the description of the ideas and the political struggles of Stephen Kalong Ningkan, the State’s first Chief Minister, and the issues affecting his political leadership.